Exploring new focuses in early childhood development: a study of non-formal training and provision approches. - Phillips, Maureen Fitzgerald (My University, 2014)
This research report explores changing trends in the training of early childhood development (BCD) workers by non-formal resource and training organisations in the Free State and former Transvaal. The report analyses previous research on ECD training, conducted in part by the author of this report on behalf of the Centre for Continuing Education at the University of the Witwatersrand as well as an audit of training offered by ECD non-goverranental organisations (NGO) conducted by the Joint Education Trust, a major funder of ECD NGO's. The author's involvement in a project piloting new approaches to ECD training and services, served as a further tool with which to analyse the relevance of existing work by ECD NGO's to the situation of young children and their families in South Africa. The analysis was conducted by superimposing a set of key questions on the documents identified. The current non-formal training offered was found to still be weighted towards supporting the running and management of centre-based pre-schools where the main focus is on young children's cognitive development and physical care, while the often brutal realities of life of South Africa's young children calls for a much more comprehensive, integrated and strategic approach to improving children's overall well-being. The report raises concerns about the limitations of continuing with such approaches and makes suggestions as to how training and provision can become more responsive to people's needs and strengths.